INVESTIGATION OF THE VIBRO-ACOUSTIC BEHAVIORS OF LUFFA BIO COMPOSITES AND ASSESSMENT OF THEIR USE FOR PRACTICAL APPLICATIONS - (:unkn) unknown (INT INST ACOUSTICS & VIBRATION, 2016)
New materials as alternatives to petroleum-based composite materials are needed due to adverse effects of chemical materials on nature. On the other hand, there is a need to characterize and evaluate new alternative materials to be effectively used in practical applications. The vibro-acoustic behaviors including damping and elastic properties, sound absorption and transmission loss levels of luffa bio-composites are investigated and their use for practical applications is evaluated in this study. First, the procedure for manufacturing luffa composites is summarized and materials and methods are presented. After that, the acoustic absorption and transmission loss levels of sample luffa composites are explored by using the impedance tube method. The damping and elastic properties of sample luffa composites are determined by using experimental and theoretical modal data. Furthermore, the interface properties of the luffa fibers and matrix are examined by using Scanning Electron Microscope. All the results are evaluated and the potential of the use of luffa composites in practical applications is assessed.
Keywords: NATURAL-RUBBER COMPOSITES; MECHANICAL-PROPERTIES; CYLINDRICA FIBERS; SPONGE; POLYESTER; POLYMER; FLAX